2017
DOI: 10.1111/ijcp.12917
|View full text |Cite
|
Sign up to set email alerts
|

Alpha blockers in the management of ureteric lithiasis: A meta-analysis

Abstract: Despite the opposing results of recently published trial, current evidence continues to demonstrate a potential benefit of α-blocker treatment particularly for distal stones over 5 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
3
3
0
2
Order By: Relevance
“…Interestingly, the meta-analysis by Raison and colleagues. 12 showed a greater benefit for MET in stone passage (RR = 1.60) for larger stones (>5 mm) in keeping with the Australian study published by Furyk and colleagues. 6 It also showed MET is also better at treating distal ureteric stones (RR = 1.50), in keeping with the study by Sur and colleagues, 7 but not in the study by Furyk and colleagues.…”
Section: Evidence Against Medical Expulsive Therapysupporting
confidence: 88%
“…Interestingly, the meta-analysis by Raison and colleagues. 12 showed a greater benefit for MET in stone passage (RR = 1.60) for larger stones (>5 mm) in keeping with the Australian study published by Furyk and colleagues. 6 It also showed MET is also better at treating distal ureteric stones (RR = 1.50), in keeping with the study by Sur and colleagues, 7 but not in the study by Furyk and colleagues.…”
Section: Evidence Against Medical Expulsive Therapysupporting
confidence: 88%
“…Traditionally the expectant management is reserved only for renal stones smaller than 5 mm [ 7 ]. Recent studies have shown that medical expulsive therapy (MET) is efficacious in promoting stone expulsion and this effect is more prominent with larger stones [ 8 , 9 ]. Tamsulosin and nifedipine are the two main agents shown to be effective as MET [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a bibliometric experiment, I made a list of all EC articles from 2016 to 2017, excluding editorials, and examined the number of downloads from the journal's website ascertained by Wiley as of 22 August 2018 (Table ). For the articles published in 2016 and 2017, I also compiled a list of the top 10 downloaded articles from the journal (Table ).…”
Section: Articles From the International Journal Of Clinical Practicementioning
confidence: 99%